Relationship between executive functions and reading fluency in reading comprehension - Carriquiry Colombino, Carolina; Reali, Florencia; Cuadro, Ariel (Revista de Investigación en Logopedia, 2025)
Contemporary approaches to the study of reading comprehension examine how multiple cognitive skills are interconnected. Within this framework, the aim of the present study was to explore the relationships between core executive functions, oral language skills and reading fluency in their effect on reading comprehension. A sample of 78 children in 5th and 6th grade of primary school were tested on reading comprehension and fluency, as well as on working memory, inhibition, cognitive flexibility, vocabulary, oral comprehension and fluid intelligence. Correlation, hierarchical regression, and mediation analyses were conducted. The results show that working memory predicts reading comprehension, even when controlled for oral language skills. However, when reading fluency is introduced into the model, only vocabulary and reading fluency are significant predictors. The mediation analysis shows that reading fluency is a complete mediator of the effect of working memory on reading comprehension. In addition, vocabulary was found to be a relevant predictor of reading comprehension, even controlling for other skills. These findings show that it is crucial to assess interactions between multiple cognitive processes when studying written language comprehension. Furthermore, they suggest that one way in which executive functions affect reading comprehension is indirect and that reading fluency mediates this relationship.
Keywords: reading comprehension; reading fluency; working memory; vocabulary